Recent Developments in the Institutional Framework of Ship Recycling and the Positive Impact on International Ship Dismantling Practices - Samiotis, Georgios; Charalampous, Konstantinos; Tselentis, Vasileios S. (SPOUDAI Journal of Economics and Business, 2013)
Ship construction today requires a wide variety of materials, which on the one hand have environmental impacts and on the other, are economically valuable. This introduced ship dismantling, which after the '70s, when ship scraping was common practice, developed further, due to significant influences from free market practices which focused solely on price competitiveness. This situation created a geographic shift of ship scrapping activities from developed countries (70s) to Far East countries (1970-1990) and after 1990, to Third World countries. In addition this geographical reallocation and the ever increasing competitiveness in ship breaking services brought about serious negative impacts on the marine and coastal environment, while at the same time dramatically affecting occupational health and safety. Recent years reveal a slow, but promising process of change both in environmental terms, as well as in safety and human life protection. A key element of this change seems to be the improvements brought about by complementing existing national but mainly international (IMO) and European Community (EU) regulatory regimes. This institutional framework in combination with the perceived political will to implement change, form the basis for positive developments in the ship dismantling sector focusing on health, environment and welfare matters. JEL Classifications: K332; Q530